Helium isotope record, CaCO3 concentration and accumulation rate of ODP Site 138-849 (Table 2) - Gisela Winckler; Robert F Anderson; Martin Stute; Peter Schlosser (PANGAEA, 2004)
The cause of the 100 kyr glacial–interglacial cycles during the past 800 kyr is one of the fundamental puzzles in paleoclimatology. The widely accepted Milankovitch theory, relating earth extquotesingles climate cycles to variations in insolation caused by periodic changes in orbital parameters, has difficulties to explain the predominant 100 kyr rhythm. Although earth extquotesingles eccentricity varies with a period of 100 kyr, the resulting change in insolation is too small to produce the corresponding climate cycle by direct forcing (Imbrie et al., 1993; doi:10.1029/93PA02751. In order to solve the extquotesingle100 kyr problem extquotesingle, Muller and MacDonald (1995, doi:10.1038/377107b0; 1997, doi:10.1126/science.277.5323.215; Proc. Nat. Acad. Sci. USA 94 (1997b) 8329) proposed an alternative orbital but non-Milankovitch mechanism attributing the glacial cycles to regular variations in the accretion of interplanetary dust particles (IDP) caused by 100 kyr cycles in the orbital inclination of the earth. To test this controversial hypothesis, we study the IDP accumulation in deep-sea sediments from a period in the early Pleistocene. We find apparent 41 kyr cycles but no 100 kyr periodicity in the IDP accumulation rate. As there is no known mechanism to produce 41 kyr cycles in IDP supply from space, we conclude that the 41 kyr cycles are caused by the dynamics of sediment accumulation, and that changes in the IDP flux do not drive the Pleistocene glacial cycles.
Supplement to: Winckler, G et al. (2004): Does interplanetary dust control 100 kyr glacial cycles? Quaternary Science Reviews, 23(18-19), 1873-1878, https://doi.org/10.1016/j.quascirev.2004.05.007